The effects of informal land markets on urban land development in rapidly growing urban areas: the case of Sululta town, Ethiopia - Abebe, Birhanu Girma; Dadi, Birhanu Uma; Bifa, Adane Obsie (Frontiers in Sustainable Cities, 2024)
Informal land market is one of the main challenges of urban land development in most developing countries like Ethiopia. For example, in cities adjacent to Addis Ababa, rapid horizontal expansion with varies land development problems are very common phenomena.The study was conducted to understand the effects of informal land market in Sululta town.Parameters such as: rate of urban expansion; density of the settlements; level of consumption of the natural environment and unsuitability were used to further study the problems.Geographic Information System (GIS), trend analysis models and overlay analysis with supportive literature reviews were carried out to answer research questions. The findings of the study show that, the town is experiencing low density urban growth, losing its ecological footprints and rapid horizontal sprawling. Effective land policy that can satisfy the ever growing land demand, building sound able formal land market system and application of predevelopment urban planning can be recommended for the local government.